Employee Silence and Entrepreneurial Orientation in Small and Medium-Sized Family Firms - Pimentel, Duarte; Rodrigues, Raquel (European Journal of Family Business, 2022)
This paper aims to assess differences between employees of family and non-family firms regarding their levels of employee silence and their perceptions of the company’s entrepreneurial orientation. Moreover, focusing on family firms, we assess the relationship between the levels of employees’ silence and their perceptions of the firm’s entrepreneurial orientation. The empirical evidence is provided by a sample of 245 Portuguese employees, 117 employees of family firms, and 128 of non-family firms, who responded to a questionnaire that included employee silence and entrepreneurial orientation measures. Results reveal that family firms’ employees show higher levels of employee silence but perceive their companies as less entrepreneurially oriented than employees of non-family companies. In addition, our results do not support the idea that there is a relationship between the levels of employee silence and the employee’s perception of the company’s entrepreneurial orientation. This paper offers initial insights into the debate on the relationship between the levels of employee silence and the employee’s perception of the company’s entrepreneurial orientation in family firms.